2016
DOI: 10.1038/srep37210
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cytometry of Human Leukocytes with Third Harmonic Generation Microscopy

Abstract: Based on third-harmonic-generation (THG) microscopy and a k-means clustering algorithm, we developed a label-free imaging cytometry method to differentiate and determine the types of human leukocytes. According to the size and average intensity of cells in THG images, in a two-dimensional scatter plot, the neutrophils, monocytes, and lymphocytes in peripheral blood samples from healthy volunteers were clustered into three differentiable groups. Using these features in THG images, we could count the number of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…The fluorescence lifetime distribution from the blood vessel (blue square) is centered around 500 to 800 ps, which is similar to the fast fluorescence decay of red blood cells as reported in the literature. 32,33 By contrast, the lifetime distribution from the metastatic tissue region (red square) has 1000 to 1500 ps, which is analogous to the histogram from Fig. 2.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The fluorescence lifetime distribution from the blood vessel (blue square) is centered around 500 to 800 ps, which is similar to the fast fluorescence decay of red blood cells as reported in the literature. 32,33 By contrast, the lifetime distribution from the metastatic tissue region (red square) has 1000 to 1500 ps, which is analogous to the histogram from Fig. 2.…”
Section: Resultsmentioning
confidence: 63%
“…It is reported that pure forms of haemoglobin and red blood cells in tissues have fast fluorescence decay (∼300 ps). 32,33 However, contrary to these findings, a recent report on multiphoton excited haemoglobin in stored blood revealed a long-lifetime (∼1300 ps) component in addition to a short lifetime value (∼280 ps). 37 The fluorescence lifetime values from our study are slightly higher than the values reported previously in the literature.…”
Section: Discussionmentioning
confidence: 71%
“…By far, the HGM have been widely applied to the investigation of human skin and mucosa, [12][13][14] assessment of atopic dermatitis, 15 diagnoses of oral squamous cell carcinoma, 16 characterizations of skin aging, 17 morphological analysis on human adipocytes, 18 live brain imaging of neurons, 19 and the in vivo cytometry on leukocytes. [20][21][22] Since the biological tissues have severe scattering at visible wavelengths and strong water absorption at wavelengths longer than 1300 nm, 23 people commonly adopt 800 to 1300 nm femtosecond laser sources for deep-tissue optical virtual biopsy. 13,[24][25][26][27][28][29] In the 800-to 1100-nm wavelength range, many endogenous pigments such as flavins can be two-photon excited.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the THG microscopy-based imaging cytometry is to automatically differentiate and count different types of blood cells with less blood ex vivo, or even in vivo [38]. One of the many strengths of THG is reflecting the granularity of leukocytes, which allows us to apply image processing techniques for the automatic classification.…”
Section: Application To the Cytometry Problemmentioning
confidence: 99%